2009
DOI: 10.1111/j.1540-8175.2009.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Two‐Dimensional Global Longitudinal Strain and Strain Rate Imaging for the Assessment of Left Atrial Function: A Study in Subjects with a Low Probability of Cardiovascular Disease and Normal Exercise Capacity

Abstract: Global longitudinal LA epsilon/SR parameters determined by 2D speckle tracking echocardiography are feasible and reproducible indices for the evaluation of LA function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 38 publications
5
83
0
Order By: Relevance
“…The feasibility and reproducibility of STE for the study of LA mechanics have been validated in several studies (28,(46)(47)(48)(49), and can be obtained in ~90% of cases. The major limitation is the necessity for adequate 2 dimensional image quality and acquisition at a relatively high frame rate (4,5).…”
Section: La Strain By 2d Stementioning
confidence: 97%
“…The feasibility and reproducibility of STE for the study of LA mechanics have been validated in several studies (28,(46)(47)(48)(49), and can be obtained in ~90% of cases. The major limitation is the necessity for adequate 2 dimensional image quality and acquisition at a relatively high frame rate (4,5).…”
Section: La Strain By 2d Stementioning
confidence: 97%
“…The development of new echocardiographic techniques, such as two-dimensional speckle tracking echocardiography (STE) has enhanced the ability to evaluate left atrial (LA) function by using quantitative assessment of myocardial deformation. Studies have indicated that STE is a feasible and reproducible method in assessing LA function (4,5). In some patient groups, as paroxysmal or permanent AF, LA strain measurements were found to be associated with episodes of paroxysmal AF and stroke risk in follow up (6,7).This method may provide a more direct evaluation of LA myocardial contractility and passive deformation (5).…”
Section: Introductionmentioning
confidence: 99%
“…383,384 New echocardiographic techniques-Two-dimensional speckle-tracking echo has been used as a more sensitive marker to detect early functional remodelling before anatomical alterations occur. [385][386][387][388][389][390][391][392][393][394][395][396][397][398][399][400] Strain (S) and strain rate (SR) imaging provide data on myocardial deformation by estimating spatial gradients in myocardial velocities. 385,388,392,393,[401][402][403][404][405] This technique has been used as a surrogate of LA structural remodelling and fibrosis.…”
Section: Left Atrial Function By Doppler Echocardiographymentioning
confidence: 99%